RANCANG BANGUN SISTEM PENGENDALI IRIGASI BERBASIS ANALISIS EVAPOTRANSPIRASI DENGAN KONTROLER ON/OFF - Guntur Rian Muhammad Nur; Susilo Adi Widyanto (JURNAL TEKNIK MESIN, 2015)
Food is a basic requirement for life so that the availability is absolutely necessary of all time. The need for food continues to increase along with the growth of population. While the source of the water decreases and becomes scarce during the dry season. So the real action to improve agricultural products is indispensable. One way to meet the water needs of plants properly is to calculate the crop evapotranspiration with Penman-Monteith equation. While the tools to realize the results of these calculations is to create an irrigation controllers system. Irrigation control system that is made has inputs from weather environment obtained with the sensor and has an output valve to drain the water. The main parameters are used as input air temperature, wind speed, relative humidity, and solar radiation. All parameters acquired digitally except solar radiation, solar radiation are acquired from correlation shaping using artificial neural networks algorithm with input temperature and light intensity. The type of valve used is on/off with controller type used is on/off. This study divided into three steps, the first steps is modeling with matlab software. Second, the design of simulation tools with results shown on oscilloscope. Third, the design of the controller device. Artificial neural networks are used feedforward structure with 2 hidden layer. The amount of the first layer size is 15x2 matrix and The amount of the second layer is 1, which produces a fairly good prediction, i.e., with the largest error of 1.13%. The simulation results of the control system on/off produces an error of 1.8% while the application of control system on/off produces an error of 2.20%.